Rheological characterization of Xanthan-guar mixtures in dilute solutions - Khouryieh, Hanna Anton Michael (Kansas State University, 2006)
Dynamic viscoelastic and intrinsic viscosity properties of native xanthan, deacetylated xanthan, guar, and their mixtures in dilute solutions were investigated by using an oscillating capillary rheometer. Influence of mixing temperature, deacetylation, and salt concentration on xanthan conformation and interaction with guar were studied in order to provide additional evidence that can be used to elucidate the mechanism of the intermolecular interaction between the two biopolymers, and build up a more detailed rheological understanding of molecular interactions between xanthan and guar gum in dilute solutions. Synergistic interaction was found at mixing temperatures of 25 and 80 °C, but a stronger synergistic interaction was observed at mixing temperature of 80 °C. The differences in viscosity and elasticity measurements between the two mixing temperatures could be attributed to the degree of disordering of xanthan. For both mixing temperatures, the relative viscosity and elasticity of xanthan and guar blends were higher than the relative viscosity and elasticity calculated for blends assuming no interaction, indicating that intermolecular binding occurred between galactomannans backbone and disordered segments of xanthan. Deacetylated xanthan exhibited a stronger synergistic interaction with guar than native xanthan. The intrinsic viscosities of deacetylated xanthan-guar mixtures were higher than those calculated from the weight averages of the two individually, whereas the intrinsic viscosities of native xanthan-guar mixtures were lower than those calculated from weight averages of the two individually, demonstrating that intermolecular binding occurred between xanthan and guar gum. Synergistic interaction for both native xanthan-guar mixtures and deacetylated xanthan-guar mixtures in the dilute regime was observed in water and 2 mM NaCl but not in 40 mM NaCl. The results suggest that intermolecular interaction has occurred between xanthan and guar mixtures in water and 2 mM NaCl, but may not occur in 40 mM NaCl and mutual incompatibility may take place. These results also suggest that degree of disordering of xanthan played a critical role in xanthan-guar interaction and may explain the differences in viscosity, elasticity, and intrinsic viscosity measurements between 2 and 40 mM NaCl, and hence, the intermolecular interaction occurred between the backbone of guar gum and the disordered segments of xanthan.
Keywords: Xanthan; Guar; solutions; synergistic interaction; rheology; deacetylation; Agriculture, Food Science and Technology (0359)